Society, schools, and progress in Nigeria - Lewis, L. J. (Leonard John) (Commonwealth and international library., 1965)
Society, Schools and Progress in Nigeria is one of a mutually supporting series of books on SOCIETY, SCHOOLS AND PROGRESS in a number of important countries or regions. Nigeria makes a good field of study for several reasons. As Africans, the Nigerians are closely scrutinized by neighbors throughout the huge continent. A hitherto underdeveloped people, they are helping to lead the rapid development of more than 2000 million people who have until now been in a similar position. Inevitably, therefore, their use and modification of previously unquestioned instruments of education seem likely to bring challenges (perhaps enlightenment) to educators everywhere.